ASSESSMENT OF LEARNING FLAT-SIDED SPACES BASED ON SPATIAL ABILITY - Priharvian, Syifa Maharani; Kumening, Ayu Sulistya; Kartono, Atha Irdina Nursabrina; Hasanah, Laili Mufidatul; Dewanti, Sintha Sih (Jurnal Pendidikan Matematika (JUPITEK), 2024)
This study aims to determine the results of the assessment of students' spatial abilities which are very important to master to understand geometry relations, and geometry properties, and solve mathematical problems including on the material of flat-sided spaces in class VIII. This research uses descriptive research through qualitative and quantitative approaches. The sampling technique in this study used a random sampling technique with 31 students as the research sample. The research instruments used were observation and interview guidelines with qualitative analysis and spatial ability tests with quantitative analysis. The analysis of the test instrument was processed with the help of SPSS and Microsoft Excel to determine the feasibility of the instrument. Based on the results obtained through several aspects of the assessment of students' spatial abilities seen from four indicators of ability. The concept understanding indicator has increased until the last meeting, while the pattern recognition and imagination indicators tend to increase and decrease at the last meeting. The interview results also prove that the spatial ability test instrument given for five meetings is quite helpful in understanding the flat-sided space building material